Pengaruh Fraud Triangle dan Religiusitas Terhadap Perilaku Kecurangan Akademik (Studi Empiris pada Mahasiswa Akuntansi FEB Unisma dan UIN Maulana Malik Ibrahim Malang Angkatan 2018) - Wahyu Amelia Ningrum; Junaidi Junaidi; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2023)
ABSTRACTThis study aims to determine the effect of pressure, opportunity, rationalization, and religiosity as independent variables, on academic cheating as the dependent variable, either simultaneously or partially. All students of the accounting study program at the Islamic University of Malang and UIN Maulana Malik Ibrahim Malang class of 2018 were designated as the population by the researchers, with a total of 307 students. The Slovin formula was used by researchers to determine the number of samples, so that the final result was 75 respondents. According to the type, this research is a verification research with data collection method using questionnaires distributed to respondents. The results of the study state that simultaneously or partially the variables of pressure, opportunity, rationalization, and religiosity affect the academic cheating behavior of accounting students from the economics and business faculty of the Islamic University of Malang and UIN Maulana Malik Ibrahim Malang class of 2018.Keyword : Pressure, opportunity, rationalization, religiosity, academic cheating behavior.